Healthy relationships in higher education : promoting wellbeing across academia - Lemon, Narelle (London: Routledge, 2022)
"Self-care involves taking action to support, protect or maintain wellbeing. Relationships have a significant influence on these acts of self-care and one's sense of wellbeing. Relationships are fundamental to individual meaning-making and crucial to the world of academia. In this edited collection, authors navigate how they view relationships as a crucial part of their wellbeing and acts of self-care, exploring the "I", "We" and "Us" at the centre of self-care and wellbeing embodiment. Each chapter unpacks this idea in varying ways that demonstrate that relationships are a fundamental element of both work and personal life and how they intersect with wellbeing. The authors present critical discussion through visual narratives, lived experiences and strategies that highlight how relationships, seeking social support, scaffolding opportunities to learn with and from each other, and changes in practise become acts of self-care individually and collectively. There has arguably never been a more important time to raise awareness of self-care and wellbeing as central to the nature of work in higher education. Healthy Relationships in Higher Education: Promoting Wellbeing Across Academia highlights new ways of working in higher education that disrupt current tensions that neglect wellbeing and will be of interest to anyone working in this environment"--
Vulnerability, self-care and the relationship with us and others in higher education / Narelle Lemon -- Creative and collaborative expression as contemplative selfcare / Jane. E. Dalton, Catherine E. Hoyser --"A stitch in time..." : scholar-activism as resistance/disruption, method, and self-care practice / Rosalie D. Clarke -- The ripple effect of social support in academia / Kristina Turner -- Creating a sense of belonging through self-care strategies in higher education / Susanne Garvis, Heidi Harju-Luukkainen, Anne Keary, Donna Pendergast, Tina Elisabeth Yngvesson -- Building belonging : a grassroots peer-support network for academic women / Jennifer L. Beaudry, Narelle Lemon, Helana Scheepers, Flavia Marcello, Esther Wilding, Christine Agius, Simone Taffe, Birgit Loch, Virginia Kilborn -- Alamus : singing together for self-care and wellbeing within higher education context / Jasna K. Schwind, Emma MacGregor, Heather Beanlands, Daria Romaniuk, Lori Schindel Martin -- Seeing past the mask : rejuvenating academia through art based self-care / Pattie Ann Pryma -- Creating care-full conditions is institutional work : research developers as campus earthworms / Tseen Khoo, James Burford, Jeanette Fyffe -- Table chats : research relations and the impact on our wellbeing as academics / Megan McPherson, Narelle Lemon -- From survival to self-care : performative professionalism and the self in the neoliberal university / Emma Coonan -- Lessons from the trickster : Be present. Be empathetic. (Be love). Be playful / Marsha Heck -- Discovering the inner-outer self in a time of endings and a time of beginnings / Rachel Taylor -- Recovering care for past publications : an exercise in vocation / Catelijne Coopmans -- Authenticity and wellbeing in neoliberal times : imagining alternatives / Bin Wu.
Includes bibliographical references and index.
Keywords: College teachers; College teachers; College teachers; Well-being.; Work-life balance